2015
DOI: 10.1093/infdis/jiv180
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Characteristics in Patients With Chronic Hepatitis B Virus (HBV) Infection Are Associated With HBV Surface Antigen Clearance After Combination Treatment With Pegylated Interferon Alfa-2a and Adefovir

Abstract: Combination therapy significantly influences NK cell phenotype and function. Differences between patients with chronic hepatitis B with HBsAg clearance and nonresponders suggest that NK cells play a role in the clearance of HBsAg during interferon-based combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…Previous studies have demonstrated that CD56 bright NK cell proliferation was increased after utilizing combination therapy with Peg-IFN-α and an NA10. The ability of Peg-IFN-α therapy to induce IL-15 has been demonstrated9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that CD56 bright NK cell proliferation was increased after utilizing combination therapy with Peg-IFN-α and an NA10. The ability of Peg-IFN-α therapy to induce IL-15 has been demonstrated9.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the current treatment regimen for CHB includes Peg-IFN-α, a potent activator of NK cells9. Third, the genotype for certain receptors regulating NK cell activity has been associated with treatment-induced HBV clearance1011.…”
mentioning
confidence: 99%
“…Thirdly, natural killer cell characteristics in CHB patients are associated with HBsAg clearance (28). Combination treatment with PEG-IFNα and ADV significantly influences NK-cell function (29,30). In addition, B-cells play an important role in the clearance of HBV and in protection against reinfection.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-α has a dual mechanism of action in CHB, first, a direct antiviral effect achieved through inhibiting the synthesis of viral DNA, virus particles, and activation of antiviral enzymes, and second, an augmentation of antiviral host immunity (8). In CHB, IFN-α treatment induces narrowly focused immune responses restricted to activation of the innate immunity with little impact on reactivating stagnant HBV-specific adaptive immune responses which are central to long-term control of infection (1215). …”
Section: Introductionmentioning
confidence: 99%